ANALISIS BENTUK KUBAH DAN AKULTURASI BUDAYA PADA BANGUNAN MASJID AL OSMANI MEDAN - Rendy Prayogi; Ganal Rudiyanto; Achmad Syarief (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2021)
AbstractMedan City is a combination of several ethnicities and cultures, because in Medan there are several Acehnese, Batak and Malay ethnic groups. Medan has a Malay Deli building with exotic religious and artistic nuances to visit, especially if we like typical Malay buildings such as the Al Osmani Mosque building which still elevates and preserves cultural arts even though there has been a renewal of traditional architecture into modern architecture, but the Malay building still has value. aesthetics with various types of ornament forms, colors, placement of Malay ornaments and also the acculturation of various cultures. Al Osmani Mosque was first built in 1854 with selected wood materials imported from Penang. During the VII Deli Malay Sultanate, namely Sultan Osman Perkasa Alam. Then in 1870 - 1872 the wooden mosque was built permanently by his son, Sultan Mahmud Perkasa Alam (VIII Sultan of Deli). The Al Osmani mosque building was designed by a German architect named GD Langereis with materials sent from Spain and Persia. This study uses a historical approach and aesthetic approach. The historical approach will involve a discussion of the origins of the building form of the Al Osmani Mosque and its functional development since it was founded until now. The aesthetic approach will involve a discussion of the dome shape of the Al Osmani Mosque, what cultural acculturations are there in the Medan Al Osmani Mosque building so that it can attract attention and have unique characteristics? The results showed that the Al Osmani Mosque and its interior as well as the space filling elements in it were not fully influenced by the aesthetics of the forms that came from the Deli Malay culture but were also influenced by the aesthetic forms of Chinese, European, Indian and Middle Eastern cultures.Keywords : Acculturation, Ornaments, Aesthetics, History, Al Osmani Mosque.  AbstrakKota Medan merupakan perpaduan dari beberapa etnis dan budaya, karena di Kota Medan di dapati beberapa etnis Aceh, etnis Batak dan etnis Melayu. Medan memiliki bangunan Melayu Deli bernuansa seni dan religi yang eksotis untuk dikunjungi khususnya jika kita menyukai bangunan-bangunan khas Melayu seperti Bangunan Masjid Al Osmani masih mengangkat dan melestarikan seni budaya meskipun terjadi pembaharuan arsitektur tradisional menjadi arsitektur modern, tetapi pada bangunan Melayu tersebut masih memiliki nilai estetis dengan berbagai jenis bentuk ornamen, warna, penempatan ornamen Melayu dan juga akulturasi dari berbagai budaya. Masjid Al Osmani pertama kali dibangun pada tahun 1854 dengan bahan kayu pilihan yang didatangkan dari Penang. Pada masa Kesultanan Melayu Deli ke-VII yaitu Sultan Osman Perkasa Alam. Kemudian pada tahun 1870 - 1872 masjid yang terbuat dari bahan kayu itu dibangun permanen oleh putranya yakni Sultan Mahmud Perkasa Alam (Sultan Deli ke-VIII). Bangunan masjid Al Osmani di desain oleh arsitek asal Jerman yang bernama GD Langereis dengan material yang dikirim dari Spanyol dan Persia. Penelitian ini menggunakan pendekatan sejarah dan pendekatan estetika. Pendekatan sejarah akan menyangkut pembahasan tentang asal-usul bentuk bangunan Masjid Al Osmani dan perkembangan fungsionalnya sejak didirikan hingga sekarang. Pendekatan estetika akan menyangkut pembahasan tentang bentuk kubah Masjid Al Osmani, akulturasi budaya apa saja yang terdapat pada bangunan Masjid Al Osmani Medan sehingga bisa menarik perhatian dan memiliki ciri khas yang unik?. Hasil penelitian memperlihatkan bahwa Masjid Al Osmani dan interiornya serta elemen pengisi ruang di dalamnya tidak sepenuhnya dipengaruhi oleh estetika bentuk yang berasal dari budaya Melayu Deli tetapi juga dipengaruhi oleh estetika bentuk dari kebudayaan China, Eropa, India dan Timur Tengah.Kata Kunci : Akulturasi, Ornamen, Estetika, Sejarah, Masjid Al Osmani.